Rationally designed peptide induces apoptosis and cell cycle modulation in resistant melanoma - Rocha, Layza Sá; Jacobowski, Ana Cristina; Thiburcio, Eduarda; Pereira, Rafael Araujo; Almeida, Claudiane Vilharroel; Gutierrez, Camila De Oliveira; de Andrade Farias Rodrigues, Thaís; Oliveira, Rodrigo Juliano; Taveira, Gabriel B.; Hiane, Priscila Aiko; de Araújo Boleti, Ana Paula; Franco, Octávio Luiz; et al. (Biochimica et biophysica acta. General subjects, 2026)
The ineffectiveness of conventional therapies against melanoma necessitates the development of novel approaches characterized by high selectivity and low systemic toxicity. Using computational optimization, KW18, a synthetic α-helical peptide, was rationally engineered. It incorporates conserved bioactive motifs from patented peptides. The Joker algorithm was used to refine the peptide. This process enhanced its positive charge, hydrophobicity, and α-helical stability. In vitro, KW18 displayed potent cytotoxicity against melanoma cells (IC₅₀ = 11.41–21.75 μM) with 84–91 % inhibition at 128 μM, minimal toxicity to FN1 fibroblasts, hemolysis below 5 %, and stability exceeding 80 %. Functional assays revealed mitochondrial damage and caspase-dependent apoptosis (86.5 % late apoptosis at 24 h). Cell cycle analysis in B16F10-Nex2 cells revealed a moderate accumulation in G0/G1 phase (62.9 %) alongside a substantial S-phase population (25.8 %), with minimal Sub-G0 (5.2 %) and reduced G2/M (6.1 %). This profile suggests a cytostatic-like effect through partial cell cycle slowdown. Structural characterization via helical wheel projections and circular dichroism confirmed its α-helical conformation, consistent with membrane-targeting activity. In vivo, Galleria mellonella larvae exposed to KW18 exhibited 100 % survival, supporting a favorable safety profile. Collectively, KW18 combines apoptosis induction with cell cycle modulation, offering a dual mechanism against melanoma while sparing healthy cells. These findings designate KW18 as a stable, selective, and safe therapeutic option for drug-resistant melanoma and a beneficial element for combined treatments. [Display omitted] •KW18 is a motif-based hybrid peptide rationally designed using bioinformatics.•Selectively cytotoxic to melanoma cells while sparing human fibroblasts.•Induces apoptosis (up to 86.5 %) through caspase-dependent mechanisms.•Modulates cell cycle by reducing G2/M and enriching S-phase population.•Shows low hemolysis and in vivo safety in Galleria mellonella model.